Pengaruh Product Knowledge, Brand Image, dan Brand Ambassador Terhadap Keputusan Pembelian Top White Coffe Mahasiswa FEBI IAIN Kudus 2016-2017 - Suparwi, Suparwi; Fitriyani, Syarifatul (Universitas Islam Negeri Sunan Kudus, 2020)
This research aims to find the effect of produck knowledge, brand image, brand ambassador against purchasing decisions top white coffie products in students of the faculy of economics and Islamic busines (FEBI) IAIN Kudus 2016-2017. Many factors motivate consumers to make purchasing decisions. Purchasing decisions are consumer behavior in deciding whether to buy a product or not. Usually consuimers will consider before going to decide on a purchase a product that will buy. This research uses quantitative research, the population in this study amounted to 1.091 Student. While the sample used 92 student. The analysis technique uses multiple linear regression analysis. The results of this study indicate that product knowledge has an effect on purchasing decisions. Brand image affects purchasing decisions and brand ambassador influences decision making. And together Product Knowledge, Brand Image, Brand Ambassador influence purchasing decisions.